ANALISIS NILAI-NILAI PATRIOTISME PADA FILM TANAH SURGA KATANYA SEBAGAI MEDIA PEMBELAJARAN IPS MENGENAI SIKAP KEPAHLAWANAN BAGI SISWA KELAS IV - Pratami, Widina; Susilawati, Susilawati; Ridwan, Ita Rustiati (Didaktika, 2022)
Film can be utilized as a medium of learning in education. Within the film, numerous educational values can be learned by students, such as the value of patriotism. Within the film, numerous instructive values can be learned by understudies, such as the esteem of patriotism. The Tanah Surga Katanya film, which tells almost the lives of Indonesian citizens in border ranges, features a part of heroic values that emanate from the characters. The values of patriotism can be learned and imitated by fourth-grade rudimentary school understudies. This investigation was conducted to discover the values of patriotism contained in the Tanah Surga Katanya film. A qualitative approach and content analysis method were used in this research. Information in this study was collected by listening, observing, listening to dialogue, and doing fragments. At that point, the information was analyzed utilizing the steps of Miles and Huberman which are to show specific information lessening, information show, and drawing conclusions. Based on the analysis, the researchers found that there are 20 information discoveries within the Tanah Surga Katanya film which comprises 3 values of devotion, 4 values of mettle, 2 values of being willing to give up, 1 esteem of never giving up, and 10 values of adore for the nation. The results of this study can be utilized as social studies learning media regarding heroic attitudes for fourth-grade students.